THE CORRELATION BETWEEN READING HABIT AND READING COMPREHENSION ACHIEVEMENT OF 12TH GRADE STUDENTS OF MA. PP. QODRATULLAH LANGKAN - Agus Wahyudi (Edukasi, 2015)
The main objectives of this study are to find out; 1) how is the students’ reading habit, 2) how is the students’ reading comprehenaion achievement, 3) is there any significant correlation between reading habit and reading comprehension of 12th grade students of MA. PP. Qodratullah. The writer used descriptive quantitatif design to describe the data. The population of the study was five classes of 12th grade students of MA. PP. Qodratullah. The sample of this study was 168 students. The writer used questionnaire (Janthong, 2010) and reading test to collect the data. The test was administered once as post-test. Before the post-test was administered to the sample students, the validity and reliability of the instruments were estimated. The result of the test were analyzed by using Independent Sample T-test through SPSS (Statistical Package for Social Science) 16.0. From the analysis, it was showed that the t-obtained was 0.309. It could be concluded that there was no significance correlation between the two variables since the t-obtained was higher than 0.05. The factors that influnced this condition were; 1) the misperception of the students toward good reading habits, 2) students preferred to read for pleasure (comics, newspapers, sport magazines), 3) the students preferred to read for pleasure, while the tests of this research were taken from reading for academic purpose materials. However, building a good reading habit is essential to be recommended because it is very important to  develop the students’ reading comprehension achievement.